Magneto-optical absorption coefficients in monolayer MoSe2 - Bich, Tran N.; Phuc, Huynh V.; Dinh, Le (Hue University Journal of Science: Natural Science, 2021)
We study the linear, third-order nonlinear, and total absorption coefficients (OACs) caused by intra- and inter-band transitions in monolayer MoSe2 in the presence of a magnetic field by using the compact density matrix approach. The results show that the OACs display the blue-shift behaviour with an increase in the magnetic field. The Zeeman fields do not affect the peak positions but reduce peak intensities slightly. Besides, the strong spin-orbit coupling in monolayer MoSe2 causes the peaks to differ significantly due to spin-up and spin-down. The OACs due to intra-band transition display only one peak in the THz range, while the inter-band spectra show a series of peaks in the near-infrared optical range, making monolayer MoSe2 a promising candidate for novel optoelectronic applications.